Congenital Brachial Arthrogryposis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Two patients with congenital cervical spinal muscular atrophy and arthrogryposis limited to the upper limbs are reported from the Hospital Enschede, The Netherlands, and University Hospital RWTH Aachen, Germany.